Smoke-derived cues in the regulation of seed germination: are Ca2+-dependent signals involved? - Omoarelojie, Luke O.; Kulkarni, Manoj G.; Finnie, Jeffrey F.; van Staden, Johannes (Plant growth regulation, 2022)
Seed dormancy and germination are two distinct physiological processes in the life cycle of plants. Dormancy alleviation and the attendant transition to seed germination are critical developmental events that are regulated by endogenous and ambient cues. ROS, Ca 2+ (and Ca 2+ -dependent) signals, and phytohormones, such as ABA and GA, are significant endogenous cues. On the other hand, temperature, light, and smoke-derived compounds are ambient cues that regulate the transition from seed dormancy to germination. An intricate balance in ABA and GA metabolism and their antagonistic hormonal interactions, in which ROS and Ca 2+ -dependent signals feature as signal initiators, integrators, or transducers, underpin the regulatory mechanisms that control dormancy alleviation and seed germination. Smoke-derived compounds are exogenous chemical cues with significant influences on seed dormancy and germination. They interact with several endogenous cues, including ROS and phytohormones, to control these processes. In this review, we summarize Ca 2+ signaling in plants with a concise detail on Ca 2+ -dependent signals in the regulation of seed germination. We also discuss the cross talks between smoke-derived cues and Ca 2+ -dependent signals, phosphoinositide/phospholipase C pathway, and ROS signaling. Finally, we touch on current knowledge on the involvement of Ca 2+ -dependent signals in smoke cue-mediated ABA-GA hormonal interactions and provide some perspectives on how to advance the subject of Ca 2+ signal involvement in the regulation of dormancy alleviation and seed germination by smoke-derived cues.